Perancangan Sarana Mobilitas Hijau Berbasis Teknologi Tepat Guna Sebagai Ikon Ecotourism Di Desa Suroteleng, Selo, Boyolali - Syawaluddin Adha Pohan; Arif Kusumawanto; Alva Edy Tontowi (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2020)
Suroteleng Village (Selo Subdistrict, Boyolali Regency, Central Java) is located between the slopes of Mount Merapi to the north and the slopes of Mount Merbabu to the south. This makes Suroteleng Village potentially as a strategic ecotourism destination. Nevertheless, the local government wants to have a distinctive tourism identity, and downhill biking (cycling from the top of the mountain slope to the lower point) is proposed to be an iconic nature tourism activity in the village. Therefore it is necessary to design mobility facilities, which can facilitate tourists to easily be able to get to the starting point of cycling, which is located on the upper slopes of the mountain. The mobility facility was designed based on two aspects, namely: 1) System design theory (system engineering), and 2) Global Sustainable Tourism Council Destination Criteria; so that it meets the requirements as a green mobility based on appropriate technologies and become icon in the ecotourism area of Suroteleng Village.